Archipelago of justice : law in France's early modern empire - Wood, Laurie M. (Yale University Press, 2020)
"Archipelago of Justice assesses France's Atlantic and Indian Ocean colonies in tandem, highlighting the interconnectedness of these dynamic oceanic trading systems and slave societies. Drawing together evidence from law courts, correspondence, and personnel records, it uncovers the interwoven lives of previously anonymous colonial participants-from soldiers and sailors to planters, artisans, women investors, and emancipated slaves-who together built France's first global empire. These imperial subjects sought new political and legal influence via law courts with strategies that reflected local and regional priorities, particularly regarding slavery, war, and trade"--